ERADICATION OF CRIMINAL ACTS OF CORRUPTION: SYSTEMIC STRATEGY AND RECONSTRUCTION OF THE EVIDENCE PARADIGM IN INDONESIAN CRIMINAL LAW - Umarul Faruq; Pujo Widodo; Adnan Majid (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Corruption remains a serious problem in the Indonesian legal system, not only because it causes state financial losses but also weakens public trust in government institutions and undermines the principle of the rule of law. The development of corruption shows an increasingly complex pattern, both in terms of the number of cases and the modus operandi used by perpetrators. This condition demands a systemic eradication strategy and the reconstruction of the evidentiary paradigm in criminal law to increase the effectiveness of law enforcement against corruption. This study aims to analyze the strategy to eradicate corruption through a systemic approach and examine the reconstruction of the evidentiary paradigm in Indonesian criminal law. This study uses a normative juridical research method with a statutory and conceptual approach, supported by a literature review of various criminal law and corruption eradication law literature. The results show that corruption eradication cannot rely solely on conventional law enforcement but requires a comprehensive legal system reform that includes institutional strengthening, regulatory refinement, and increased coordination between law enforcement agencies. In addition, the reconstruction of the evidentiary paradigm, particularly through expanding the meaning of the unlawful element and the implementation of more progressive evidentiary mechanisms, is a crucial factor in addressing the complexity of corruption. Therefore, strengthening the legal framework and evidentiary system is a strategic step in realizing more effective and equitable corruption eradication efforts in Indonesia.